Resolution, signed by V.I. Lenin, of the Council of People's Commissars to preserve the Moscow-house where Tolstoj lived and worked from 1882 to 1901. From: Bro 605/4 fol, nr.52 (1920)
Resolution, signed by V.I. Lenin, of the Council of People's Commissars to preserve the Moscow-house where Tolstoj lived and worked from 1882 to 1901. From: Bro 605/4 fol, nr.52.